Pathophysiology of Headaches From Molecule to Man - Ashina, Messoud; Geppetti, Pierangelo (Headache, 2015)
This book provides a detailed overview of the current state of knowledge regarding the pathophysiology of both primary headaches - migraine, tension-type headache (TTH), and cluster headache - and the very important and frequent type of secondary headache, medication overuse headache (MOH). After an introductory chapter describing relevant neuroanatomy and vascular anatomy, the evidence gained from animal models regarding the pathophysiology of migraine and the other primary headaches is reviewed. Knowledge of the genetic component in the different types of headache is then examined with reference to recent evidence, for example regarding the implication of the trigeminovascular system and cortical spreading depression in migraine. Detailed information is provided on insights into primary headaches from imaging studies, including functional magnetic resonance imaging and positron emission tomography and on their neurophysiology and biochemistry. A further series of important chapters describe present knowledge of the pathophysiology of each specific type of headache and consider future directions. Written by acknowledged experts in their fields from Europe and the United States, clinicians and students will find Pathophysiology of Headaches to be an excellent source of up-to-date information on why patients experience headaches. In addition, it will be of value for pain researchers investigating the underlying mechanisms of headache.